D Diplomasi Iklim: Upaya menyelamatkan bumi dari krisis iklim ? - Adi Subiyanto (PendIPA Journal of Science Education, 2024)
Various human activities have caused the concentration of greenhouse gases (GHG) such as CO2, CH4, and N2O in the earth's atmosphere to increase, which has an impact on increasing global temperatures and has led to the climate crisis. To reduce GHG emissions, countries that ratified the Paris Agreement set targets to be achieved as Nationally Determined Contributions (NDC). The Paris Agreement must be integrated into diplomatic practice as climate diplomacy. The method used in this research is qualitative-descriptive analysis. The data used were reports from the Intergovernmental Panel on Climate Change (IPCC) and Indonesia's contribution to the NDC document. The research results showed that 1) Global warming had caused a climate crisis so that it has become a threat to the survival of life; 2) Indonesia's contribution in reducing the rate of global warming through NDC had not been able to reach the target of 29% with its own efforts or 41% with assistance and cooperation; and 3) Climate diplomacy, which is expected as an effort to reduce the climate crisis, was not easy to carry out. The obstacle to implementing climate diplomacy is that each country has its own interests.